Follow-up patterns after positive primary aldosteronism screening - Raul Herrera; Michael Salim; Meng Xu; Sisi Ma; Jacob Kohlenberg; Kidmealem Zekarias (PLoS ONE, 2025)
Primary aldosteronism (PA) screening remains underdiagnosed at <2% of eligible patients, with inconsistent interpretation of positive screening results across institutions. This study investigated whether patients with positive PA case screening test results received appropriate follow-up interventions. We assessed plasma renin activity (PRA) and aldosterone concentration (PAC), calculating the aldosterone-to-renin ratio (ARR). Three commonly used criteria defined positive case detection: PAC ≥ 10 ng/dL and PRA < 1 ng/mL/h; ARR ≥ 20 and PAC ≥ 10 ng/dL; and ARR ≥ 30 and PAC ≥ 10 ng/dL. We identified 237 patients meeting at least one criterion between April 2018 and May 2023, then assessed follow-up care at least 6 months post-screening. Adequate follow-up included documented abnormal results in progress notes, further PA diagnostics, new MRA treatment, or specialist referral. Inadequate follow-up was observed across all screening criteria: 37% (82/222) of patients meeting PAC ≥ 10 ng/dL and PRA < 1 ng/mL/h, 38% (89/237) of those meeting ARR ≥ 20 and PAC ≥ 10 ng/dL, and 30% (53/180) of those meeting ARR ≥ 30 and PAC ≥ 10 ng/dL lacked appropriate care. History of hypokalemia (p < 0.001), English as primary language (p ≤ 0.007), and higher socioeconomic status (p ≤ 0.06) were consistently associated with adequate follow-up. These findings highlight the need for standardized criteria and automated alerts to improve follow-up after positive PA screening.